Laminated board and printed circuit board including same

By using specific thermosetting resin compositions and reinforcement materials in electronic circuits, the laminated plates formed solve the problems of comprehensive performance such as low dielectric constant, low dielectric loss, high peel strength in the prior art, and achieve high frequency Reduced electrical signal transmission loss in the circuit.

CN119427855AActive Publication Date: 2025-02-14ITEQ WUXIELECTRONICS TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310961016.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14
Estimated Expiration
2043-08-01

AI Technical Summary

Technical Problem

The prior art is difficult to achieve comprehensive performance requirements such as low dielectric constant, low dielectric loss, and high peel strength in electronic circuits, especially in high-frequency circuits with large losses in electrical signal transmission.

Method used

Using a thermosetting resin composition including unsaturated polyphenylene ether resin, styrene-butene block copolymer, cycloolefin compound, vinylphenyl compound and crosslinking agent, combined with specific reinforcement materials such as E-glass fibers , NE-glass fiber or polystyrene fiber cloth, a laminated plate is formed by semi-cured film and hot pressing treatment.

Benefits of technology

The comprehensive performance requirements such as low dielectric constant, low dielectric loss, and high peel strength are achieved to meet the requirements of electronic circuits for these performances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119427855A_ABST
    Figure CN119427855A_ABST
Patent Text Reader

Abstract

The invention provides a laminated board and a printed circuit board comprising the same. The laminated board comprises a resin substrate and a metal foil layer. The resin substrate comprises a plurality of prepregs, and each prepreg is formed by coating a reinforcing material with a thermosetting resin composition. The total weight of the thermosetting resin composition is 100 parts by weight, and the thermosetting resin composition comprises the following components in parts by weight: (A) 30-50 parts of unsaturated polyphenyl ether resin; (B) 10 to 30 parts by weight of a styrene-butylene block copolymer; (C) 5 to 25 parts by weight of a cycloolefin compound; (D) 1 to 10 parts by weight of a vinylphenyl compound; and (E) 5 to 25 parts by weight of a crosslinking agent. The laminated board and the printed circuit board provided by the invention have the characteristics of low dielectric constant, low dielectric loss and high peel strength of the electronic circuit base material by virtue of the specific thermosetting resin composition and the matching of the specific thermosetting resin composition and the reinforcing material in proportion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate and a printed circuit board, and in particular to a laminate containing a thermosetting resin composition of a specific composition and a printed circuit board including the laminate. Background Art

[0002] The advancement of modern information processing technology has prompted digital circuits to enter a stage of high-speed information processing and high-frequency signal transmission. In high-frequency circuits, the transmission loss of electrical signals is represented by the sum of dielectric loss, conductor loss, and radiation loss. The higher the frequency of the electrical signal, the greater the transmission loss of the electrical signal.

[0003] Since transmission loss will attenuate the electrical signal and destroy the reliability of the electrical signal, it is necessary to reduce dielectric loss, conductor loss and radiation loss. The dielectric loss of the electrical signal is proportional to the product of the dielectric loss angle of the insulator forming the circuit and the frequency of the electrical signal used. Therefore, by selecting insulating materials with a small dielectric loss angle, the transmission loss of the electrical signal can be reduced.

[0004] US Patent No. 9428646B2 discloses the use of unsaturated polyphenylene ether and polybutadiene resin mixed to control the dielectric properties of the insulating board, but the unsaturated polyphenylene ether and butadiene have poor compatibility, and the mixed product is prone to precipitation. Furthermore, bismaleimide is added to provide better copper bonding, however, the laminate prepared by these materials has a relatively high dissipation factor.

[0005] US Patent No. 5223568A discloses a laminate prepared by using polybutadiene, polyisoprene and thermoplastic elastomer, and the obtained laminate has the characteristic of low loss. However, the peel strength of the polybutadiene board when bonded to the copper foil is poor, and other properties such as mechanical strength, flammability and heat resistance are even worse.

[0006] Therefore, it is necessary to provide a laminate and a printed circuit board for electronic circuits to meet the requirements of electronic circuit products for comprehensive performance such as low dielectric constant, low dielectric loss, and high peel strength. Summary of the invention

[0007] The main purpose of the present invention is to provide a laminate, which includes: a resin substrate and a metal foil layer disposed on at least one surface of the resin substrate. The resin substrate includes a plurality of semi-cured films, and each of the semi-cured films is made of a reinforcing material coated with a thermosetting resin composition. Wherein, the thermosetting resin composition, with a total weight of 100 parts by weight, includes: (A) 30 to 50 parts by weight of an unsaturated polyphenylene ether resin; (B) 10 to 30 parts by weight of a styrene-butylene block copolymer; (C) 5 to 25 parts by weight of a cycloolefin compound; (D) 1 to 10 parts by weight of a vinyl phenyl compound; and (E) 5 to 25 parts by weight of a cross-linking agent; wherein the unsaturated polyphenylene ether resin includes at least one carbon-carbon double bond or carbon-carbon triple bond, and at least one carboxyl group, and the carboxyl group is selected from the group consisting of carboxylic acid, anhydride, amide and ester.

[0008] In one embodiment of the present invention, the reinforcing material is E-glass fiber (E-glass), NE-glass fiber (NE-glass) or polystyrene fiber cloth (PS-glass).

[0009] In one embodiment of the present invention, the styrene-butylene block copolymer is a block copolymer derived from an alkenyl aromatic compound block and a conjugated diene block.

[0010] In one embodiment of the present invention, the styrene-butylene block copolymer is a styrene-butylene block copolymer grafted with maleic anhydride.

[0011] In one embodiment of the present invention, the styrene-butylene block copolymer is at least one selected from the group consisting of styrene-butadiene diblock copolymer (SB), styrene-butadiene-styrene triblock copolymer (SBS), styrene-isoprene diblock copolymer (SI), styrene-isoprene-styrene triblock copolymer (SIS), styrene-(ethylene-butylene)-styrene triblock copolymer (SEBS), styrene-(ethylene-propylene)-styrene triblock copolymer (SEPS) and styrene-(ethylene-butylene) diblock copolymer (SEB).

[0012] In one embodiment of the present invention, the cycloolefin compound is at least one selected from the group consisting of dicyclopentadiene (DCPD) monomer, dicyclopentadiene polymer, norbornene monomer and 5-norbornene polymer.

[0013] In one embodiment of the present invention, the vinylphenyl compound is selected from stilbene and / or bromostyrene.

[0014] In one embodiment of the present invention, the cross-linking agent is at least one selected from the group consisting of triallyl isocyanurate, triallyl cyanurate, bismaleimide resin and divinyl benzene.

[0015] In one embodiment of the present invention, the thermosetting resin composition further comprises: an accelerator, wherein the accelerator is at least one selected from the group consisting of di-tert-butyl peroxide, dilauroyl peroxide, dibenzoyl peroxide, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, 1,1-di-tert-butyl peroxy-3,5,5-trimethylcyclohexane, 1,1-di-tert-butyl peroxycyclohexane, 2,2-di(tert-butyl peroxy)butane, bis(4-tert-butylcyclohexyl) peroxydicarbonate, hexadecyl peroxydicarbonate, tetradecyl peroxydicarbonate, dipentyl peroxide, diisopropylbenzene peroxide, bis(tert-butyl peroxyisopropyl)benzene, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexyne and diisopropylbenzene hydroperoxide.

[0016] In one embodiment of the present invention, the thermosetting resin composition further includes: an inorganic filler, wherein the inorganic filler is at least one selected from the group consisting of silicon dioxide, aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, calcium carbonate, aluminum nitride, boron nitride, aluminum silicon carbide, silicon carbide, titanium dioxide, zinc oxide, zirconium oxide, barium sulfate, magnesium carbonate, barium carbonate, mica, talc and graphene.

[0017] Another object of the present invention is to provide a printed circuit board, which includes the laminated board according to the present invention.

[0018] One of the beneficial effects of the present invention is that the laminate and the printed circuit board including the laminate provided by the present invention can provide and meet the requirements of the electronic circuit substrate for comprehensive performance such as low dielectric constant, low dielectric loss, and high peel strength through the technical scheme of "the reinforcing material is E-glass fiber (E-glass), NE-glass fiber (NE-glass) or polystyrene fiber cloth (PS-glass)", "the unsaturated polyphenylene ether resin includes at least one carbon-carbon double bond or carbon-carbon triple bond, and at least one carboxyl group" and a specific formula ratio. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a schematic structural diagram of a laminated board of the present invention;

[0020] Figure 2 It is a schematic structural diagram of a printed circuit board of the present invention.

[0021] Explanation of symbols in the accompanying drawings:

[0022] P Printed circuit board;

[0023] L laminate;

[0024] 1. Resin substrate;

[0025] 2 metal foil layer;

[0026] 11. Precured film;

[0027] 111 Reinforcement materials;

[0028] 112 Thermosetting resin composition. DETAILED DESCRIPTION

[0029] The technical solution adopted by the present invention is to provide a laminated board, such as Figure 1 As shown, the laminate L of the present invention comprises: a resin substrate 1 and a metal foil layer 2 disposed on at least one surface of the resin substrate. The resin substrate 1 comprises a plurality of semi-cured films 11, and each of the semi-cured films 11 is made of a reinforcing material 111 coated with a thermosetting resin composition 112. The thermosetting resin composition comprises, based on a total weight of 100 parts by weight, (A) 30 to 50 parts by weight of an unsaturated polyphenylene ether resin; (B) 10 to 30 parts by weight of a styrene-butylene block copolymer; (C) 5 to 25 parts by weight of a cycloolefin compound; (D) 1 to 10 parts by weight of a vinylphenyl compound; and (E) 5 to 25 parts by weight of a cross-linking agent; wherein the unsaturated polyphenylene ether resin comprises at least one carbon-carbon double bond or carbon-carbon triple bond, and at least one carboxyl group.

[0030] In one embodiment of the present invention, the reinforcing material is E-glass, NE-glass or polystyrene fiber cloth (PS-glass). E-glass, also known as alkali-free glass, is a borosilicate glass with good electrical insulation and mechanical properties, and is widely used in the production of glass fibers for electrical insulation. NE-glass has the characteristics of low dielectric constant and low dielectric loss factor. Compared with the reinforcing materials of polyethylene and polypropylene fibers with low melting points, the present invention selects specific reinforcing materials to maintain the CTE and heat resistance of the laminate.

[0031] Specifically, polyphenylene ether (PPE) resin has good mechanical properties and excellent dielectric properties, with a Dk / Df of about 2.45 / 0.0007 at a frequency of 1 MHz, and is the preferred resin material for substrates of high-frequency printed circuit boards. Preferably, the unsaturated polyphenylene ether resin used in the present invention is modified and includes the following multifunctional compounds: at least one carbon-carbon double bond or carbon-carbon triple bond, and at least one carboxyl group, for example, carboxylic acid, anhydride, amide, ester. More specifically, the unsaturated polyphenylene ether resin used in the present invention can be selected from terminal vinyl benzyl modified polyphenylene ether resin or difunctional methacrylate modified polyphenylene ether resin.

[0032] The styrene-butylene block copolymer is a block copolymer comprising (A) a block derived from an alkenyl aromatic compound and (B) a block derived from a conjugated diene. More specifically, the styrene-butylene block copolymer may be selected from at least one of the group consisting of a styrene-butadiene diblock copolymer (SB), a styrene-butadiene-styrene triblock copolymer (SBS), a styrene-isoprene diblock copolymer (SI), a styrene-isoprene-styrene triblock copolymer (SIS), a styrene-(ethylene-butylene)-styrene triblock copolymer (SEBS), a styrene-(ethylene-propylene)-styrene triblock copolymer (SEPS), and a styrene-(ethylene-butylene) diblock copolymer (SEB). In one embodiment of the present invention, the styrene-butylene block copolymer is a styrene-butylene block copolymer grafted with maleic anhydride.

[0033] The vinyl phenyl compound is selected from stilbene and / or bromostyrene compounds, for example, Saytex 3010 bromostyrene commercially available from Albemarle. More specifically, the bromostyrene compound provides high flame retardancy, thermal stability, better compatibility, and no precipitation.

[0034] The cycloolefin compound is at least one selected from the group consisting of dicyclopentadiene (DCPD) monomers, dicyclopentadiene polymers, norbornene monomers and norbornene polymers having a bridged ring hydrocarbon, or a combination thereof.

[0035] Preferably, the crosslinking agent can be at least one selected from the group consisting of triallyl isocyanurate (TAIC), triallyl cyanurate (TAC), bismaleimide resin and divinylbenzene. If the proportion of the crosslinking agent is too high, the thermal conductivity of the crosslinked resin composition will be reduced (for example, the thermal conductivity coefficient K value will be reduced). If the proportion of the crosslinking agent is too low, the thermal properties of the crosslinked resin composition will be poor (for example, the glass transition temperature Tg will be reduced).

[0036] Furthermore, different accelerators can be used depending on the physical property requirements of the product. Preferably, the accelerator is a peroxide crosslinking accelerator, more specifically, an organic peroxide free radical initiator. For example, the accelerator is at least one selected from the group consisting of di-tert-butyl peroxide, dilauroyl peroxide, dibenzoyl peroxide, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, 1,1-di-tert-butylperoxy-3,5,5-trimethylcyclohexane, 1,1-di-tert-butylperoxycyclohexane, 2,2-di(tert-butylperoxy)butane, bis(4-tert-butylcyclohexyl)peroxydicarbonate, hexadecyl peroxydicarbonate, tetradecyl peroxydicarbonate, dipentyl peroxide, diisopropylbenzene peroxide, bis(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di-tert-butylperoxyhexane, 2,5-dimethyl-2,5-di-tert-butylperoxyhexyne, and diisopropylbenzene hydroperoxide. In one embodiment, the accelerator is diisopropylbenzene peroxide (DCP) commercially available from Arkema.

[0037] Silane coupling agents can improve the metal adhesion of polyolefin materials. Silane coupling agents commonly used in the relevant technical field can be selected. For example, the inorganic functional group of the silane coupling agent is a trifunctional group, i.e., Si-(OR2). In one embodiment of the present invention, the silane coupling agent can be vinyl silane, amino silane, methacryloxy silane, etc.

[0038] Preferably, the flame retardant is a phosphorus-containing flame retardant and a brominated flame retardant. Examples of brominated flame retardants include ethylene-bis(tetrabromophthalimide), decabromodiphenylethane and 2,4,6-tris(2,4,6-tribromophenoxy)-1,3,5-triazine. Examples of phosphorus-containing flame retardants include bisphenol diphenyl phosphate, ammonium polyphosphate, hydroquinone bis(diphenyl phosphate), bisphenol A bis(diphenyl phosphate), tris(2-carboxyethyl)phosphine (TCEP), tris(chloroisopropyl) phosphate, trimethyl phosphate (TMP), dimethyl methylphosphonate (DMMP), resorcinol bis(xylyl phosphate), phosphazene, melamine polyphosphate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and its derivatives or resins, melamine cyanurate and trishydroxyethyl isocyanurate.

[0039] In one embodiment of the present invention, the flame retardant may be a DOPO compound, such as a DOPO resin (DOPO-HQ, DOPO-NQ, DOPO-PN or DOPO-BPN) and an epoxy resin containing DOPO. More specifically, DOPO-BPN may be selected from bisphenol-formaldehyde novolac compounds, such as DOPO-BPAN, DOPO-BPFN or DOPO-BPSN.

[0040] The inorganic filler is selected from the group consisting of silica, alumina, barium sulfate, talc, clay, mica powder, and boron nitride. More preferably, the inorganic filler is selected from the group consisting of fused silica, amorphous silica, and hollow silica, such as Lianrui D1028L spherical silica, which can adjust the dielectric constant, dielectric loss, and thermal expansion coefficient of the dielectric substrate layer. Specifically, the inorganic filler can increase the thermal conductivity of the resin composition, improve its thermal expansion and mechanical strength.

[0041] See also Figure 2 The laminate L of the present invention can be applied to a printed circuit board P, which is formed by patterning the metal foil layer 2 of the laminate L. For example, the metal foil layer 2 can be patterned by electroplating or etching processes to further form a printed circuit layer.

[0042] [Example]

[0043] Tables 1 to 3 of the present invention provide the component ratios and reinforcing materials of the thermosetting resin compositions of Examples 1 to 14 and Comparative Examples 1 to 7, respectively. The thermosetting resin compositions are prepared according to the component ratios, and the reinforcing materials are immersed in or coated with rollers to wet the thermosetting resin compositions. The solvent is evaporated by baking and the resin is semi-cured, cooled and rolled up to form a semi-cured film. The semi-cured film is further subjected to heat pressing to form a dielectric substrate layer. Specifically, the heat pressing treatment is to laminate four semi-cured films and two 18 μm copper foils (metal foil layers) of the same batch in the order of copper foil, four semi-cured films, and copper foil, and then press them at 220° C. for 2 hours under vacuum conditions to form a copper foil substrate, wherein the four semi-cured films are cured to form an insulating layer between two copper foils, and the aforementioned copper foil is etched by a wet etching process to form a wiring pattern, forming a specific wiring circuit, and obtaining a printed circuit board.

[0044] The physical properties of the copper foil substrate were tested and recorded in Tables 1 to 3.

[0045] [Physical property test]

[0046] Peel strength: Peel strength test is performed according to industry standards.

[0047] Heat resistance of copper foil laminate (T288): Also known as "tinning result", the heat resistance test is based on the industry standard IPC-TM-6502.4.24.1, and the copper foil laminate is immersed in a 288℃ tin furnace until the board explodes.

[0048] Dielectric constant (Dk): Measured according to IPC-TM-650 2.5.5 test specification. The dielectric constant represents the electronic insulation properties of the film. The lower the value, the better the electronic insulation properties.

[0049] Dielectric loss (Df): Measured according to IPC-TM-650 2.5.5 test specification. Dielectric loss indicates the ability of a material to absorb microwaves of a certain frequency at a certain temperature. Usually in the specifications of communication products, the lower the dielectric loss value, the better.

[0050] Coefficient of thermal expansion (CTE): measured according to IPC-TM-650-2.4.24 test standard.

[0051] Table 1. Examples 1 to 4 and Comparative Examples 1 to 2

[0052]

[0053] Table 2. Examples 5 to 7 and Comparative Examples 3 to 5

[0054]

[0055] Table 3. Examples 11 to 14 and Comparative Examples 6 and 7

[0056]

[0057]

[0058] OPE-2St 2200: terminal vinyl benzyl modified polyphenylene ether (Mw: about 3600, purchased from Mitsubishi Gas Chemical Co., Ltd.)

[0059] SA9000: bifunctional methacrylate modified polyphenylene ether (Mw: 1700, purchased from SABIC)

[0060] SA90: unmodified polyphenylene ether (Mw: 1700, commercially available from SABIC Innovative Plastics Ltd.)

[0061] PPO640: unmodified polyphenylene ether, (molecular weight: 18,000, commercially available from SABIC Innovative Plastics Ltd.)

[0062] D1118: Solid SB-SBS copolymer (commercially available from Kraton Polymers)

[0063] G1648: SEBS compound (commercially available from Kraton Polymers)

[0064] KIC19-023: Maleic anhydride grafted SEBS copolymer (commercially available from Kraton Polymers)

[0065] Saytex3010: Brominated styrene

[0066] DCPD monomer: dicyclopentadiene (commercially purchased from Zibo Luhua Hongjin New Materials)

[0067] Topas COC 5013: Cyclic olefin copolymer with non-reactive functional groups

[0068] TAIC: Triallyl isocyanurate

[0069] MIR3000: Biphenyl BMI

[0070] DCP: dicumyl peroxide (commercially available from Arkema)

[0071] KBM503: Vinyl silane (purchased from Shin-Etsu Commercial, Japan)

[0072] saytex 8010:Decabromodiphenylethane

[0073] D1028L: Spherical silica purchased from Lianrui Commercial

[0074] Referring to Table 1, Examples 1 to 4 and Comparative Examples 1 and 2 show that the dielectric properties of the unmodified polyphenylene ether deteriorate due to the presence of hydroxyl groups. In addition, the unmodified polyphenylene ether has better tin-bleaching heat resistance.

[0075] Referring to Table 2, the maleic anhydride-modified styrene-butylene block copolymer can effectively improve the peel strength, and its effect on the dielectric properties is small. From Comparative Example 3, it can be seen that the decrease in the proportion of polyphenylene ether in the formula of the thermosetting resin composition will lead to poor heat resistance, while the addition of vinyl phenyl compounds and crosslinking agents (triallyl isocyanurate, TAIC) helps to improve heat resistance.

[0076] Referring to Table 3, the melting points of the reinforcement materials of polyethylene (PE) and polypropylene (PP) fibers used in Comparative Examples 6 and 7, respectively, are relatively low. They melt during the lamination process (above 190 degrees), which will cause the CTE of the substrate to increase and the heat resistance to deteriorate.

[0077] The beneficial effect of the present invention lies in that the laminate and the printed circuit board including the laminate provided by the present invention include a specific thermosetting resin composition, which can provide and meet the requirements of the electronic circuit substrate for comprehensive performance such as low dielectric constant, low dielectric loss, and high peel strength through the technical solution of "the unsaturated polyphenylene ether resin includes: at least one carbon-carbon double bond or carbon-carbon triple bond, and at least one carboxyl group" and a specific formula ratio.

[0078] In more detail, the unsaturated polyphenylene ether resin modified with a specific group improves the low dielectric properties caused by the hydroxyl group in the polyphenylene ether and increases the heat resistance. The styrene-butylene block copolymer modified with maleic anhydride further improves the peel strength while maintaining its dielectric properties.

[0079] The above description is only a preferred specific embodiment of the present invention, which does not limit the patent scope of the present invention. Therefore, all equivalent changes made by applying the content of the present invention are also included in the scope of the present invention and are hereby stated.

Claims

1. A laminated board, characterized in that: include: A resin substrate, comprising a plurality of semi-cured films, each of which is made of a reinforcing material coated with a thermosetting resin composition; as well as a metal foil layer disposed on at least one surface of the resin substrate; Wherein, the total weight of the thermosetting resin composition is 100 parts by weight, and the thermosetting resin composition comprises: (A) 30 to 50 parts by weight of an unsaturated polyphenylene ether resin; (B) 10 to 30 parts by weight of a styrene-butylene block copolymer; (C) 5 to 25 parts by weight of a cycloolefin compound; (D) 1 to 10 parts by weight of a vinylphenyl compound; and (E) 5 to 25 parts by weight of a cross-linking agent; The unsaturated polyphenylene ether resin includes multifunctional groups, which include at least one carbon-carbon double bond or carbon-carbon triple bond and at least one carboxyl group, and the carboxyl group is selected from the group consisting of carboxylic acid, anhydride, amide and ester.

2. The laminate according to claim 1, characterized in that The reinforcing material is E-glass fiber, NE-glass fiber or polystyrene fiber cloth.

3. The laminate according to claim 1, characterized in that The styrene-butylene block copolymer is a block copolymer derived from an alkenyl aromatic compound block and a conjugated diene block.

4. The laminate according to claim 1, characterized in that The styrene-butylene block copolymer is a styrene-butylene block copolymer grafted with maleic anhydride.

5. The laminate according to claim 1, characterized in that The styrene-butylene block copolymer is at least one selected from the group consisting of styrene-butadiene diblock copolymer, styrene-butadiene-styrene triblock copolymer, styrene-isoprene diblock copolymer, styrene-isoprene-styrene triblock copolymer, styrene-(ethylene-butylene)-styrene triblock copolymer, styrene-(ethylene-propylene)-styrene triblock copolymer and styrene-(ethylene-butylene) diblock copolymer.

6. The laminate according to claim 1, characterized in that The cycloolefin compound is at least one selected from the group consisting of dicyclopentadiene monomers, dicyclopentadiene polymers, norbornene monomers and 5-norbornene polymers.

7. The laminate according to claim 1, characterized in that The vinylphenyl compound is stilbene and / or bromostyrene.

8. The laminate according to claim 1, wherein: The cross-linking agent is at least one selected from the group consisting of triallyl isocyanurate, triallyl cyanurate, bismaleimide resin and divinyl benzene.

9. The laminate according to claim 1, characterized in that The thermosetting resin composition further comprises: an accelerator, wherein the accelerator is at least one selected from the group consisting of di-tert-butyl peroxide, dilauroyl peroxide, dibenzoyl peroxide, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, 1,1-di-tert-butyl peroxy-3,5,5-trimethylcyclohexane, 1,1-di-tert-butyl peroxycyclohexane, 2,2-di(tert-butyl peroxy)butane, bis(4-tert-butylcyclohexyl) peroxydicarbonate, hexadecyl peroxydicarbonate, tetradecyl peroxydicarbonate, dipentyl peroxide, diisopropylbenzene peroxide, bis(tert-butyl peroxyisopropyl)benzene, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexyne and diisopropylbenzene hydroperoxide.

10. The laminate according to claim 1, wherein: The thermosetting resin composition further includes: an inorganic filler, wherein the inorganic filler is at least one selected from the group consisting of silicon dioxide, aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, calcium carbonate, aluminum nitride, boron nitride, aluminum silicon carbide, silicon carbide, titanium dioxide, zinc oxide, zirconium oxide, barium sulfate, magnesium carbonate, barium carbonate, mica, talc and graphene.

11. A printed circuit board comprising the build-up board according to claim 1.

Citation Information

Patent Citations

  • Process for forming hard shaped molded article of a cross-linked liquid polybutadiene or polyisoprene resin and a butadiene or isoprene containing solid polymer and resulting articles

    US5223568A

  • Low dielectric halogen-free resin composition and circuit board using the same

    US9428646B2

  • Low-dielectric resin composition, as well as copper foil substrate and printed circuit board applying same

    CN104341766A

  • High-frequency resin composition and application thereof

    CN110317445A

  • Circuit material and circuit board comprising same

    CN111372372A